A MODEL FOR DEVELOPING TEACHERS’ INNOVATIVE COMPETENCE BASED ON INTEGRATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO THE EDUCATIONAL SYSTEM - Jabborova Saodat Zoirovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This scientific article is devoted to the theoretical substantiation and practical aspects of the model for developing innovative competence of pedagogical personnel based on the integration of artificial intelligence technologies into the education system. Also, the structural blocks of the model developed by the author - conceptual-purposeful, substantive, technological and result components - are scientifically covered. The model is aimed at improving the digital and methodological training of pedagogical personnel, combining their analytical, design and reflective skills with artificial intelligence tools.